Running biomechanics as measured by wearable sensors: effects of speed and surface. Issue 5 (4th July 2021) - Hollis, Christina R.; Koldenhoven, Rachel M.; Resch, Jacob E.; Hertel, Jay
ABSTRACT: Running biomechanics research has traditionally occurred in the laboratory, but with the advent of wearable sensors measurement of running biomechanics may shift outside the laboratory. The purpose was to determine if RunScribe™ wearable sensors could detect differences in kinematic, kinetic and spatiotemporal measures during runs at two speeds and on two different surfaces. Fifteen recreational runners (7 males, 8 females; age = 20.0 ± 3.1 years) participated. While wearing sensors on the heels of their shoes, participants completed four 1600 m runs on both track and grass surfaces. On each surface, the first 1600 m was at a self-selected slow speed followed by the second 1600 m at a self-selected fast pace. The sensors quantified several kinetic, kinematic and spatiotemporal measures. Repeated measures ANOVAs compared the effects of surface and speed. The spatiotemporal measures of stride length, cycle time and contact time were predictably affected by increased running speed and increased surface stiffness, as were the kinematic and kinetic measurements of maximum pronation velocity, maximum pronation excursion, impact g, and braking g (p < 0.050). The RunScribe™ sensors identified expected changes in running biomechanics measures at different speeds and on varying surfaces.